Effects of incorporating natural minerals on production and bioactivity of bioactive glass ceramics - Stábile, Franco Matías (2016)
Two glass-ceramics composition were produced from natural minerals. Quartzes and feldspars were pre-selected on the basis of their purities studied by X-ray diffraction (XRD) and chemical analysis. Prepared compositions of glasses precursors were two different theoretical leucite (KAlSi2O6)/Bioglass 45S5 (L/Bg) ratios. Transformations of raw materials mixtures and glass precursors were studied by differential thermal analyses. On the basis of thermal analysis results, glass ceramics were produced and characterized by XRD. Glass-ceramics were composed of two major crystalline phases, leucite and sodium calcium silicate. Bioactivity tests were performed submerging the glass-ceramics into simulated body fluid (SBF) for different periods (1, 5 and 10 days). Bioactive behavior was monitored by XRD and scanning electron microscopy (SEM). Studied samples were found to be bioactive, in which hydroxyapatite layer was developed within 5 days of contact with SBF.